Dhamânu Muntijâti al-Halâl li Himâyati Huqûqi al-Mustahlikîn - M Cholil Nafis (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2020)
AbstractPatent has a prominent place in people’s lives, as it constitutes a basic engine of progress, and becomes measure of the progress and richness of nations. Countries that possess a huge percentage of patents occupy high positions among other countries and have political influence against other countries. Therefore, the countries of the world have agreed to conduct agreements to protect it, on top of which is the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS). When the State of Indonesia agreed to sign this agreement, it had to provide legal cover in the field of patent through Law number 13 of 2016. After careful study of this law and Islamic jurisprudence, including its principles, and its purposes, the research sees that the Indonesian Law and Islamic Jurisprudence agree that patent is considered as wealth and property. So, they agree on the necessity of patent protection, and imposing the punishment for the aggressor. They also agree on the patent exploitation, whether it is personal exploitation or through a license contract. However, Islamic jurisprudence has established controls for the exploitation of innocence, the most important of which is that exploitation does not harm others. ملخص البحثالتشريع القانوني وضمان المنتجات الحلال للمستهلكين المسلمين من أهم أمر أساسي. وذلك أن من واجبات المسلم أن لا يقتصرالاهتمام باستهلاك المنتجات الخالية من المخاطر الكيميائية والمواد الضارة بالصحة، بالإضافة إلى ذلك فلابد أيضا أن يهتم بحلال المنتجات من ناحية ماهيتها ومعالجتها وفقا للتشريع الإسلامي. وكذلك يجب أن تكون منتجات الملابس مطهرة وليست مصنوعة من أشياء نجسة، لأنها تفسد العبادة والصحة النفسية. دستور الدولة والقوانين واللوائح التي نتص على ضمان منتجات الحلال هي دليل على التزام الحكومة بالتواجد في توفير الحماية للمسلمين هم أعظم المستهلكين في إندونيسيا. أصبح القانون رقم 33 سنة 2014 بشأن ضمان المنتج الحلال والذي دخل حيز التنفيذ في 17 أكتوبر 2019، هو نقطة البداية أن الدولة توفر ضمانات وحمايات لمواطنيها للحصول على الغذاء والأدوية والمواد المستهلكة وفقًا لإرشادات الإيمان. ومع ذلك، فإن تنفيذ القانون وتطبيقه لا يزال يحتوي على استثنائية السلطة التقديرية (حرية التصرف) بشأن رسومات الكلفة حيث أصبحت عملية تفتيش الحلال تحت رعاية سلطة منظمة تحليل الغذاء والأدوية مستحضرات التجميل عضو مجلس العلماء الإندونيسي حتى صدور قرار وزير المالية بشأن رسومات كلفة خدمة شهادة الحلال. ولا تزال هذه استثنائية السلطة التقديرية (حرية التصرف) تؤثر بشكل أو بآخر على برنامج إلزام شهادة الحلال لكل منتجات يتم تسويقها في إندونيسيا من خلال إلصاق علامة/ختم الحلال.